The role of long noncoding RNA in traumatic brain injury - Li Z; Han K; Zhang D; Chen J; Xu Z; Hou L (Neuropsychiatric Disease and Treatment, 2019)
Zhenxing Li,* Kaiwei Han,* Danfeng Zhang,* Jigang Chen, Zheng Xu, Lijun HouDepartment of Neurosurgery, Changzheng Hospital, Second Military Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workAbstract: Traumatic brain injury (TBI), a mainly lethal and highly debilitating condition, is increasing worldwide. However, the underlying mechanism has not been fully elucidated and effective therapy is needed. Long noncoding RNAs (lncRNAs), which form a major class of noncoding RNAs, have emerged as novel targets for regulating physiological functions and mediating numerous neurological diseases. Notably, gene expression profile analyses have demonstrated aberrant changes in lncRNA expression in the cerebral cortex and hippocampus of rats, mice and human after TBI. lncRNAs may be associated with multiple pathophysiological processes following TBI and might play a crucial role in complications of TBI, such as traumatic optic neuropathy due to the regulation of specific signaling pathways. Some lncRNAs have also been found to be therapeutic targets for motor and cognitive recovery after TBI. lncRNAs may be promising biomarkers for TBI diagnosis, treatment, and prognosis prediction. However, further research isneeded to clarify the underlying mechanisms and therapeutic effects of lncRNAs on TBI. We review the current progress of studies on lncRNAs in TBI to draw more attention to their roles in this debilitating condition.Keywords: long non-coding RNA, traumatic brain injury, neuropathy